Berberine: New perspectives for old remedies - Lombardi, P. (2012)
Chemical compounds derived from plants have been used since the origin of human beings to counteract a number of diseases. Among them, the natural isoquinoline alkaloid berberine has been employed in Ayurvedic and Chinese Medicine for hundreds of years with a wide range of pharmacological and biochemical effects. More recently, a growing body of reports supports the evidence that berberine has anticancer effects, being able to block the proliferation of and to kill cancer cells. This review addresses the properties and therapeutic use of berberine and focuses on the recent advances as promising anticancer drug lead. (C) 2012 Elsevier Inc. All rights reserved.